Lipid-lowering effect of Phyllanthus embilica and Alpinia galanga extracts on HepG2 cell line - Napatara Tirawanchai (2020)
© 2019 Elsevier B.V. Dyslipidemia is a key risk factor for cardiovascular diseases. Although statins are powerful therapeutic option for achieving target low- and high-density lipoprotein levels, it is of interest to seek for alternative treatments for dyslipidemia. Phyllanthus emblica and Alpinia galanga were found to have hypolipidemic effects. However, the mechanisms underlying their bioactivity have not yet been elucidated. Lipid-lowering effects of the hydroethanolic extracts from a Phyllanthus emblica (PE), Alpinia galangal (AG) and a combination between P. emblica and A. galangal (PEAG; ratio 7:3 w/w) on expression of low-density lipoprotein receptor (LDLR), 3-hydroxyl-3-methylglutaryl-CoA reductase (HMGCR), apolipoprotein A1 (ApoA1) and scavenger receptor class B1 (SR-BI) genes were assessed in HepG2 cell line using quantitative RT-PCR (qRT-PCR). It was demonstrated from the MTT cytotoxic assay that PE and PEAG were not cytotoxic to HepG2 cell line. AG, gallic acid and simvastatin were more cytotoxic to HepG2 cell line. PEAG was found to be the most promising therapeutic agent for clearance of circulating LDL-C due to its enhancing expression of the LDLR gene. It could contribute towards enhancement of the HDL-C levels due to its upregulation expression of the APOA1 and SR-B1 mRNA transcripts in HepG2 cells.